2018
DOI: 10.1002/admt.201700322
|View full text |Cite
|
Sign up to set email alerts
|

DVS‐Crosslinked PEDOT:PSS Free‐Standing and Textile Electrodes toward Wearable Health Monitoring

Abstract: Conducting polymer electrodes based on poly(3,4‐ethylenedioxythiophene): poly(styrene sulfonate) (PEDOT:PSS) present many advantages for biological signal recording over traditional metal electrodes and are being steadily evaluated in health monitoring applications. A main requirement for wearable electrodes based on PEDOT:PSS is that selected additives, such as crosslinking agents, avoid the redispersion of the polymer or its postprocess delamination. In this work, a novel approach is presented to fabricate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 27 publications
6
36
0
Order By: Relevance
“…A possible reason could be that cotton fibers coated with the conducting polymer increase their stiffness and this can lead to a delamination or to cracks during the compression and decompression cycles, resulting in a variable trend. Similar results have been reported in the literature for similar mechanical stress levels [32]. The relative error associated to sensor A with EG, indicates how it is not reliable when the second dopant is present in the solution, even if it has an average better performance than sensor B without EG.…”
Section: Resultssupporting
confidence: 88%
“…A possible reason could be that cotton fibers coated with the conducting polymer increase their stiffness and this can lead to a delamination or to cracks during the compression and decompression cycles, resulting in a variable trend. Similar results have been reported in the literature for similar mechanical stress levels [32]. The relative error associated to sensor A with EG, indicates how it is not reliable when the second dopant is present in the solution, even if it has an average better performance than sensor B without EG.…”
Section: Resultssupporting
confidence: 88%
“…The recording of physiological signals is key to evaluate the physiological state of patients and healthy individuals. Moreover, the continuous monitoring enables pointof-care disease diagnostics and allows healthy persons to profit from it as preventive medicine while continuing their daily lives [137]. For instance, among these signals, the recording of cardiac activity by electrocardiography (ECG) is crucial to detect abnormalities such as tachycardia or myocardial infarction [138].…”
Section: Electrophysiological Recordingmentioning
confidence: 99%
“…In another study, del Agua et al reported the fabrication of conducting, water stable, free-standing textile electrodes by adding the crosslinker divinyl sulfone (DVS) to PE-DOT:PSS formulations [137]. The addition of DVS enables the preparation of low resistance free-standing as well as textile electrodes without hampering the conductivity of the films nor its mechanical features.…”
Section: Electrophysiological Recordingmentioning
confidence: 99%
“…Roll-to-roll electrochemical fabrication of Ag/AgCl coated nylon yearns has been demonstrated [172], and screen and stencil printing and blade coating have been combined for wearable EIT electrode arrays on polyester fabrics [173]. Along with silver, PEDOT:PSS (with additional crosslinkers for improved properties) is playing a prominent role with textile electrodes as well [171], [174]. Of course, with textile electrode integrated into clothing, the ability of the printed electrodes to withstand multiple washing cycles for reusability is an important factor [175].…”
Section: Recent Advancements In Bioimpedance Sensor Realizationmentioning
confidence: 99%